VISUALISASI FUNGSI DAN MAKNA TANDA VERBAL DALAM VIDEO KLIP GLORIA DAN FIGHT - Windyaningsih, Ni Ketut (Humanis; Volume 15. No.2. Mei 2016, 2016)
This research describes the visual signs of communication used in music videos entitled Gloria and Fight along with the functions and meanings contained in their lyrics. The data analyzed using qualitative analysis method. This research used the theory of semiotics by Rolland Barthes (1986), theory of visual communication  by Gillian Dyer (2009), and theory of function and meaning by Geoffrey Leech (1977). There are thirteen visual signs of communication found in the Gloria and Fight music videos. Functions and meanings contained in the music video are informational function, expressive function, aesthetic function, conceptual meaning, and connotative meaning.
Keywords: semiotics, visual sign, function and meaning